The Revenue Recognition Based on PSAK 72 in Real Estate Companies Listed on The Indonesia Stock Exchange for 2018 to 2021 - Dynda Shafiyah Azzahrah; Khristina Yunita; Rudi Kurniawan; Sari Rusmita; Vitriyan Espa (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to examine the impact of implementing PSAK 72 on revenue recognition within the Indonesian real estate sector. Using a comparative descriptive method with a quantitative approach, this research analyzed seven major real estate companies listed on the Indonesia Stock Exchange from 2018 to 2021. The results showed variations in financial performance indicators such as Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) before and after the implementation of PSAK 72. The findings indicate that the standard significantly influences financial reporting and profitability due to stricter revenue recognition criteria. This research provides insights into the practical effects of PSAK 72 for stakeholders in the real estate industry.